An observation into the conduction of nerve fibers and goniometry in women with hypothyroidism - Syed Madhar Shah K,; Kavitha P,; Shalini S,; Janardhanan S, (Asian Journal of Medical Sciences, 2024)
Background: The thyroid hormone is so essential that it is involved in the functioning of all the body systems, especially in the development of the brain in fetal life. The World Health Organization has estimated that around 2 billion individuals are suffering from thyroid disorders. Hence, it is essential to identify and diagnose hypothyroid patients so that the treatment strategy can be started at the earliest. Aims and Objectives: The present study aimed to find out the peripheral nerve conduction velocity, range, and degree of movement of joints in newly diagnosed hypothyroid women and compare them with those of normal euthyroid women. Materials and Methods: The present study was a case–control study conducted from July 2015 to March 2016. A total of 50 cases of newly diagnosed hypothyroid women and 50 age-matched euthyroid women were part of the study after obtaining written and informed consent. Thyroid estimation was performed in the Clinical Biochemistry Department by the ELISA method, and nerve conduction studies were performed in the Neurology Department. Results: The age and height of the participants were not statistically significant. Weight and body mass index were significantly higher in the cases when compared to the control group. Sensory and motor conduction velocities of the right median nerve are significantly less in these cases when compared to control group participants. Sensory and motor conduction velocities of the right ulnar nerve are significantly less in these cases when compared to control group participants. Sensory and motor conduction velocities of the left median nerve are significantly less in these cases when compared to control group participants. Sensory and motor conduction velocities of the left ulnar nerve are significantly less in these cases when compared to control group participants. The goniometric parameters (right and left sides) of the cases and control group participants were not significantly different. Conclusion: Hypothyroid women have a delay in peripheral nerve conduction velocities, including sensory and motor components, and the degree and range of movements of limb joints were not affected. A nerve conduction study may be utilized as a routine screening test for hypothyroid individuals so that hormone replacement therapy can be instituted at the earliest.